Cloning, nucleotide sequence, and expression of the Bacillus subtilis lon gene. - Riethdorf, S (1994)
The lon gene of Escherichia coli encodes the ATP-dependent serine protease La and belongs to the family of sigma 32-dependent heat shock genes. In this paper, we report the cloning and characterization of the lon gene from the gram-positive bacterium Bacillus subtilis. The nucleotide sequence of the lon locus, which is localized upstream of the hemAXCDBL operon, was determined. The lon gene codes for an 87-kDa protein consisting of 774 amino acid residues. A comparison of the deduced amino acid sequence with previously described lon gene products from E. coli, Bacillus brevis, and Myxococcus xanthus revealed strong homologies among all known bacterial Lon proteins. Like the E. coli lon gene, the B. subtilis lon gene is induced by heat shock. Furthermore, the amount of lon-specific mRNA is increased after salt, ethanol, and oxidative stress as well as after treatment with puromycin. The potential promoter region does not show similarities to promoters recognized by sigma 32 of E. coli but contains sequences which resemble promoters recognized by the vegetative RNA polymerase E sigma A of B. subtilis. A second gene designated orfX is suggested to be transcribed together with lon and encodes a protein with 195 amino acid residues and a calculated molecular weight of 22,000.